You would have to make a point at 6/3 and go down one and to the left 7... then your answer would be -1/2 sooo D=-1 hope this helps
Standard form for y+7=-2/5(x-10) is y=-7-2/5(x-10)
Answer:
6x² - x - 12
Step-by-step explanation:
Each term in the second factor is multiplied by each term in the first factor.
(2x - 3)(3x + 4)
= 2x(3x + 4) - 3 (3x + 4) ← distribute both parenthesis
= 6x² + 8x - 9x - 12 ← collect like terms
= 6x² - x - 12 ← in expanded form
Answer:
108x + 29
—————
180
Step-by-step explanation:
Answer:
-2a -12
Step-by-step explanation:
a minus * a plus is a negative therefore -12